2019
DOI: 10.1109/access.2019.2939871
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate Forced Oscillation Location and Participation Assessment Method for DFIG Wind Turbine

Abstract: With the integration of wind energy, the widely used doubly fed induction generator wind turbines (DFIG-WT) could induce Power System forced oscillations (FOs), which threaten the safety of power grid. In this paper, an accurate FOs location method is proposed to pinpoint sources of FOs to the specific components inside a DFIG-WT and a participation assessment method is proposed to evaluate the role of DFIG-WTs in the FOs event. Firstly, the energy structure of the DFIG-WT is constructed and the correspondence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The method of participation factor in the power system can also reflect part of system observability and controllability degree (He et al, 2019;Huang et al, 2019;Lei et al, 2019;Zhou et al, 2019). To monitor oscillation, Lei et al (2019) and Huang et al (2019) respectively determined the type and locations of components causing oscillation by calculating the participation factor. To suppress oscillations, strong correlation variables were determined by the participation factor method, and then, a damping controller was designed (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The method of participation factor in the power system can also reflect part of system observability and controllability degree (He et al, 2019;Huang et al, 2019;Lei et al, 2019;Zhou et al, 2019). To monitor oscillation, Lei et al (2019) and Huang et al (2019) respectively determined the type and locations of components causing oscillation by calculating the participation factor. To suppress oscillations, strong correlation variables were determined by the participation factor method, and then, a damping controller was designed (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…At present, some scholars in the industry have applied the energy analysis method to LFO and made great progress [11][12][13][14][15][16]. Literature [11][12][13] used the energy method to reveal the essence of LFO from a different perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the DFIG energy function is also emerging. Literature [16] constructed a brief energy structure of DFIG and established the corresponding relationship between the internal physical components of DFIG and the parts of the energy function. Then the established energy structure is applied to the location of the forced oscillation source.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, numerous theoretical analyses for VLFO source identification are available [8][9][10][11][12][13][14][15], a detailed review can be found in [16]. However, it is well recognised that Dissipation Energy Flow (DEF) [17] [18] is considered one of the most promising and already has some practical success in real-world applications.…”
Section: Introductionmentioning
confidence: 99%